Retinal degeneration in choroideremia follows an exponential decay function - Aylward, J; Xue, K; Patrício, M; Jolly, J; Wood, J; Brett, J; Jasani, K; MacLaren, R (Elsevier, 2018)
Fundus autofluorescence (AF) arises from lipofuscin, which is derived from retinoid byproducts of the visual cycle and accumulates within retinal pigment epithelial cells. Alterations in AF pattern are seen in a wide range of retinal degenerations. Choroideremia is an X-linked retinal dystrophy caused by loss-of-function mutations within the CHM gene, encoding Rab escort protein-1. It is uniquely characterized by a central “island” of residual AF that undergoes gradual shrinkage with disease progression. The decrease in AF area is correlated precisely with loss of overlying photoreceptors, leading to progressive visual field restriction and blindness around the fifth decade. Retinal gene replacement therapy using an adeno-associated viral vector could potentially slow down or stop disease progression in choroideremia. Although visual acuity may be improved by gene therapy, it is affected relatively late in the disease; therefore, the area of residual AF may provide an alternative anatomic biomarker for monitoring progression at earlier stages. A previous cross-sectional study suggested an exponential decrease in AF area with age in choroideremia. However, longitudinal data on natural disease progression is lacking. For instance, it is uncertain whether individuals progressed at different rates depending on genetic, epigenetic, or environmental factors, and whether the rate of progression varied between early and late stages of the disease.